Predictors and Moderators of Quality of Life Among College Students With ADHD. Issue 14 (December 2019) - Pinho, Trevor D.; Manz, Patricia H.; DuPaul, George J.; Anastopoulos, Arthur D.; Weyandt, Lisa L
Objective: The current study examines (a) whether ADHD among college students is associated with differences in perceptions of quality of life (QoL); (b) the moderating roles of comorbidity, drug use, psychopharmacological treatment, and psychosocial treatment; and (c) the total impact of these variables on QoL.Method: Participants were college students with and without ADHD ( N = 372) in a longitudinal study.Results: College students with ADHD were more likely to assert negative global QoL evaluations relative to non-ADHD peers. The relationship between ADHD and QoL was not altered as a function of medication treatment, comorbid psychopathology, psychosocial treatment, or drug use.Conclusion: College students with ADHD behave similarly to other adults with ADHD in that they make lower subjective global evaluations of their QoL relative to their non-ADHD agemates. Other factors associated with ADHD and QoL do not appear to moderate this relationship.